Flexible education in humanities and social sciences: opportunities and threats in Czech, Polish, and Slovak Universities - Rogowski, Łukasz (Przegląd Krytyczny, 2025)
This paper identifies the challenges of flexible education within the humanities and social sciences in higher education. Framed as a response to societal shifts such as individualisation, its functioning is analysed through comparative empirical research conducted at one university in each of the Czech Republic, Poland, and Slovakia. Drawing on in-depth interviews with university management and students, as well as a quantitative survey, the study constructs a SWOT analysis. This reveals that a key challenge is the potential shift of responsibility for learning effectiveness onto non-institutional actors within the education system.